Comparison of the Implementation of Restorative Justice in Criminal Case Resolution between the Old and New Criminal Codes (Law No. 1 of 2023) - Sandy Yudha Pratama; Wildan Fikarudin (Ilmu Hukum Prima (IHP), 2026)
Restorative justice is an approach to resolving criminal cases that emphasizes restoring relationships between perpetrators, victims, and the community, as well as resolving conflicts in a fair and balanced manner. In the Indonesian criminal law system, the application of restorative justice has experienced significant developments following the ratification of Law Number 1 of 2023 concerning the Criminal Code (New Criminal Code). Unlike the Old Criminal Code (Wetboek van Strafrecht), which does not explicitly regulate restorative justice and is still oriented towards a retributive approach, the New Criminal Code normatively accommodates the principle of restorative justice as part of the objectives of punishment and considerations in resolving criminal cases. This study aims to analyze and compare the application of restorative justice in resolving criminal cases between the Old and New Criminal Codes. The research method used is normative juridical with a statutory and conceptual approach. The results of the study show that in the Old Criminal Code, restorative justice was only implemented in a limited manner through law enforcement policies, whereas in the New Criminal Code, restorative justice has been institutionalized as a criminal law principle that shifts the orientation of criminal case resolution from mere punishment to restoration, peace, and social balance.